The Role of Exchange Rates, Inflation and Oil Prices on Real GDP in Iraq: Evidence from 1990 to 2022 - Hareth Adnan Mohammed (Goodwood Publishing, 2026)
Purpose: This study analyzes the short- and long-run relationships among exchange rates, consumer prices, crude oil prices, and real GDP in Iraq, exploring the mediating role of oil dependence in the price–output relationship over the period 1990–2022. Research Methodology: The study employs the ARDL bounds-testing approach with data from the World Bank, IMF, and the Iraqi Ministry of Planning. Unit root tests confirm that none of the variables are integrated of order two. The bounds test shows an F-statistic of 3.724, indicating a long-run relationship. Results: The findings indicate a long-run equilibrium relationship among the variables. The error correction term is negative and statistically significant at the 1% level, with an adjustment speed of 55.8% per year. The Consumer Price Index (CPI) has a positive and significant long-term effect on real GDP, while exchange rates and oil prices exhibit negative but insignificant effects. Granger causality tests suggest strong unidirectional causality from CPI to real GDP, with weaker causality from exchange rates and oil prices. Conclusions: The study concludes that fiscal transmission plays a significant role in transmitting external price shocks to real economic activity in Iraq, emphasizing the need for monetary discipline, exchange rate management, and economic diversification. Limitations: The study is constrained by a small sample size and limited variables, potentially omitting broader economic dynamics. Contributions: This research contributes to the literature by highlighting the importance of fiscal mechanisms and oil dependence in shaping macroeconomic outcomes in oil-dependent economies like Iraq.